Trajectories of State Formation across Fifteenth-Century Islamic West-Asia Eurasian Parallels, Connections and Divergences - Van Steenbergen, Jo (Rulers & Elites, 2020)
Constructed around seven extensively contextualized case studies, Trajectories of State Formation across Fifteenth-Century Islamic West-Asia offers a critical trans-dynastic understanding of the socio-political histories and historiographies of the Sultanates of Cairo and of the Timurid, Turkmen and early Ottoman ; Readership: All interested in medieval history, state formation studies and Islamic history (including Mamluk, Ottoman, Timurid and Turkmen histories). Keywords: West-Asia, state, Sultanate, Mamluks, Ottomans, Timurids, Qaraqoyunlu, Aqqoyunlu, Turkmen, Turks, Turko-Mongols, 15th century, entanglement, centre, periphery.